Thermal ablation in pancreatic cancer: A scoping review of clinical studies - Farmer, William; Hannon, Gary; Ghosh, Shubhrima; Prina-Mello, Adriele (Frontiers in Oncology, 2022)
Background Pancreatic cancer is a deadly cancer with a 5-year survival rate less than 10%. Only 20% of patients are eligible to receive surgery at diagnosis. Hence, new therapies are needed to improve outcomes for non-surgical candidates. Thermal ablation techniques can offer a non-invasive alternative to surgery. Aim The aim of this review is to map the literature for the use of thermal ablative techniques: Radiofrequency ablation (RFA), High-intensity focused ultrasound (HIFU), Microwave ablation (MWA), and Laser ablation (LA) in the management of patients with PC. Methods A search strategy was applied to PUBMED and EMBASE using keywords concerning pancreatic cancer, radiofrequency ablation, ultrasound ablation, laser ablation, and microwave ablation. The studies that fit this inclusion criteria were summarized in table format and results reviewed for interpretation. Results 72 clinical studies were included. Most of the included studies related to RFA (n=35) and HIFU (n=27). The most common study design was retrospective (n=33). Only 3 randomized control trials (RCT) were included, all of which related to RFA. Safety outcomes were reported in 53 of the 72 studies, and survival outcomes were reported in 39. Statistically significant survival benefits were demonstrated in 11 studies. Conclusion The evidence for the benefit of MWA and LA in PC patients is limited. RFA and HIFU are safe and feasible therapies to be used in PC patients. Further RCTs where thermal techniques are standardized and reported are necessary in the future to elucidate thermal ablation’s clinical utility, and before an evidence-based decision on its routine use in PC management can be considered.